Video-Based Learning Effect on Smoking Perception in Adolescent - Irma Darmawati; Dhika Dharmansyah; Wini Hadiyani; Ahmad Syaiful Rohmat (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: To determine the effect of video showing the dangers of smoking on students' smoking perception. Methods: This type of research is quasi-experimental with one group pretest-posttest design. A sample of 33 respondents is taken by simple random sampling based on inclusion criteria. Data analysis used a dependent t-test parametric test. The video showed the dangers of smoking for 15 minutes 6 times. Result: The video-viewing intervention significantly affected students' smoking perceptions, as evidenced by a p-value of 0.018 < (0.05). Discussion: Changes in students' perceptions are based on the experience and knowledge gained during the video viewing process. Video media involves the senses of hearing and sight to provide a more realistic picture and encourage changes in perception. Conclusions: There is an effect of showing the dangers of smoking videos on students' smoking perceptions. Video media is recommended to be used in health education efforts.